Making Details Matter: How to Reform Aid Agencies to Generate Contextu al Knowledge - Ang, Yuen Yuen (SSRN, 2014)
My essay considers a central problem of reinventing foreign aid in the twenty-first century: how to reform aid agencies to enable a “best-fi t” approach to development assistance. For the past decades, the aid c ommunity has tried to transplant best practices from the developed wor ld to the developing world. Increasingly, however, it is recognized th at copying best practices does not work and may even backfire; rather, aid programs work best when they are tailored to local contexts. Yet while the idea of a best-fit approach is widely embraced in principle, actualizing it is easier said than done. For meaningful changes to ta ke root in practice, we must first identify the obstacles to localizin g development assistance and suggest ways to address these problems. T o this end, I propose a three-pronged strategy to promote the generati on of contextual knowledge among aid professionals, a necessary condit ion for crafting solutions that can fit various local contexts, namely : (1) build a bank of knowledge about unorthodox practices that work, (2) diversify expertise within aid agencies; and (3) carve experimenta l pockets. My proposal does not fit neatly into any one of the six the mes specified in the GDN competition; rather, it concerns all of the t hemes. Whether it is to use aid to improve governance, apply informati on technology, or design financial instruments, the overarching challe nge is to empower and incentivize aid professionals to learn and apply contextual knowledge to creatively solve problems in developing socie ties.
Keywords: Contextual knowledge; Localization; Public policy; foreign aid; international development